Potential landfill site selection for solid waste disposal using GIS-based multi-criteria decision analysis (MCDA) in Yirgalem Town, Ethiopia - Mikias Biazen Molla (Cogent Engineering, 2024)
AbstractProper solid waste disposal is an important socioeconomic and environmental concern for all developing countries like Ethiopia. Due to a lack of proper disposal sites, infrastructure, and knowledge on suitable site selection, most cities/towns wrongly prefer water bodies, roadsides, and open areas as the best suitable for solid waste disposal. Such improper site selection will create morphological changes that lead to environmental hazards in the urban and surrounding areas. This study aims to identify suitable sites for solid waste disposal in Yirgalem town using the existing GIS-based multi-criteria decision analysis (MCDA) techniques. Thematic layers of road and stream network, settlement, land cover, slope, view shade, dumping site, river, and soil type and soil depth were considered as primary criteria and weights for criteria, and sub-criteria were assigned by MCDA analysis. Then, each criterion is mapped using the GIS technique, and a suitability map is prepared by overlay analyses. The consistency ratio of 0.049405 which is <0.10 endorsed the accuracy of the pairwise comparison matrix. The results indicate that 29.06% of the study area is unsuitable for the solid waste disposal site. However, 35.47% of the study area was marginally suitable, 27.84% moderately suitable, and 7.63% of the area was highly suitable is preferable for the solid waste disposal site.